“A torch, a rope, a belly laugh”: engaging with the multiple voices of support groups for people living with rare dementia - Camic, Paul M.; Harding, Emma; Rossi-Harries, Sam; Hayes, Oliver S.; Sullivan, Mary Pat; Wilson, Lawrence; Zimmermann, Nikki; McKee-Jackson, Roberta; Stott, Joshua; Fox, Nick C.; Mummery, Catherine J.; Rohrer, Jonathan D.; et al. (Frontiers in Dementia, 2025)
PurposeRare forms of dementia bring unique difficulties related to age of onset, impact on family commitments, employment and finances, and also bring distinctive needs for support and care. The aim of the present study was to explore and better understand what the concept of support means for people living with different rare dementia (PLwRD) and their care-partners who attend ongoing support groups.MethodsRepresenting seven types of rare dementia, source material was collected from 177 PLwRD and care-partners attending in-person support groups, with the goal of developing research-informed group poems, co-constructed by a facilitating poet. Data were analyzed through a three-step process involving linguistic analysis followed by structured-tabular thematic analysis, relational analysis, and concluded with an online survey about participation in the study.ResultsLinguistic analysis found that co-constructed poems remained faithful to the original source material offered by participants. These results provided confidence to subsequently conduct a thematic analysis of eight completed poems, identifying 15 initial themes. A further relational analysis between themes drew on six relational forms and identified an overarching theme “A Community, Not an Intervention” that describes the process of support for this population. Survey results revealed a varied but generally positive response to writing whilst reactions to the completed poems reflected strong emotional connections that resonated with personal experience.ConclusionThis is the first study that we are aware of to explore the use of co-constructed research poetry to better understand how in-person support groups provide support for people impacted by different rare dementias. The poems portray the complex, dynamic and relational aspects of how support groups provide a necessary form of connection for this population. An overarching theme characterized the support groups as a community rather than an intervention. Findings are discussed within the theoretical context of positive social identity, social health and biosocial groups. The results also demonstrate that solicited words from participants can be faithfully portrayed in poems co-created by an experienced poet. This novel finding expands methodological options for the use of research poetry in healthcare and also offers support group members further creative choices for engagement, connection and communication.